A survey on dental services in Metro Manila its costs and trends - Sta. Agueda, Maria Carnelita C.; Racelis, Maria Angeles R.; Marquez, Eleuteria (Adviser).; De Castro, Elizabeth (Adviser).
On October 1982, a survey was conducted among sixty dentists in Metro Manila, specifically Manila, Makati, Quezon City, Pasay City and Paranaque. The survey conducted by the researchers pertains to dental services, its costs and trends in Metro Manila. Out of sixty dentists surveyed, only fifty responded to the survey and results showed that there is a higher schedule of fees among urban dentists than suburban dentists and gross income of the urban dentists compare considerably higher than the suburban dentists. The survey also showed a greater trend towards preventive dentistry as practiced by the dentists than trends towards endodontic therapy and fixed partial denture prosthodontics. The survey gave information on the current schedule of fees charged by the dentists in the urban and suburban for the year 1982-1983.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.